From science to policy: How to support social entrepreneurship in Croatia - Sanja Tišma; Sanja Maleković; Daniela Angelina Jelinčić; Mira Mileusnić Škrtić; Ivana Keser (Journal of Risk and Financial Management, 2022)
Entrepreneurs are constantly looking for new models to address growing global challenges in a sustainable manner. Over the past several decades, those challenges have been identified and responded to through the development of social entrepreneurship. There is a number of research dealing with the theoretical concepts of those topics; however, the definitions and framework for action are different from country to country. Having in mind that the main idea of social entrepreneurship is to enable decent work for employees and to gain broader welfare for communities, the purpose of this paper is to analyse the development of social entrepreneurship in Croatia. The research is focused on recent developments, connecting key definitions and principles of social entrepreneurship with common trends and concrete case studies. This study's results show that there are different approaches to social entrepreneurship globally. However, social entrepreneurship in Croatia develops within a clear legal framework. The current state of social enterprises is connected with respective public policies, while the number and types of social entrepreneurs are constantly rising in the last few years. The results of the analysis also show that there are still actions to be taken in order to encourage future policy measures aiming to support social entrepreneurs in Croatia.
Keywords: 330; social entrepreneurship; social entrepreneur; social entrepreneurship environment; sustainable economic development; risk management; Croatia